211 Examining the effects of Vitamin D Receptor Activators on Vascular Smooth Muscle Cell Calcification using Intact Vessels from Chronic Kidney Disease Patients. (31st May 2014) - Laycock, Joanne; Shroff, Rukshana; Shanahan, Catherine; Long, David
Abstract : The most common cause of death in children with chronic kidney disease (CKD) is cardiovascular disease. Abnormal mineral metabolism in CKD predisposes patients particularly those on dialysis, to vascular calcification which develops in the tunica media and is known as arteriosclerosis. Vascular calcification is a highly regulated, cell mediated process that predominantly involves vascular smooth muscle cells (VSMCs) which undergo apoptosis, depletion of calcification inhibitors and osteochondrocytic differentiation. CKD patients are often deficient in vitamin D which is activated in the kidney by 1α hydroxylase. These patients are routinely prescribed vitamin D receptor activators (VDRAs) in order to prevent secondary hyperparathyroidism and bone mineral disorders. Vitamin D has a bimodal effect on vascular calcification with both low and high levels associated with increased risk of calcification. Current literature on VDRA effects on VSMC calcification in vitro is conflicting with some increasing calcification and others having a protective effect. It is important to understand the mechanisms of action of different VDRAs at both physiological and supra physiological doses. Therefore this study will use a clinically relevant model of intact vessel rings from predialysis CKD and dialysis CKD patients to compare the effects of physiological doses of VDRAs on calcification in pre dialysis and dialysis vessels and to explain the mechanisms of action of VDRAs on VSMCs. VDRAs, alfacalcidol (inactive form) x10 –8 M and to a greater extent calcitriol (active form) x10 –8 M increased calcification in CKD vessel rings; this was more pronounced in dialysis than pre dialysis vessels. In addition calcitriol, but not alfacalcidol up regulated alkaline phosphatase activity (an osteogenic marker) in dialysis vessels. This data suggests that these VDRAs increase calcification via different mechanisms. Next the concentration dependant effect of calcitriol (x10 –9 M, x10 –8 M and x10 –7 M) on both healthy and dialysis human VSMCs were tested. RT-PCR showed that calcitriol affected the expression of multiple genes in particular the expression of the vitamin D receptor and the inactivating 24 hydroxylase enzyme were up regulated. This response was far greater in dialysis than healthy VSMCs, the differential response to vitamin D of these cells may in part explain the difference in susceptibility to calcification of healthy and dialysis vessels.